2015
DOI: 10.1186/s12986-015-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial: the effect of inulin on weight management and ectopic fat in subjects with prediabetes

Abstract: BackgroundFat infiltration of the liver, muscle and pancreas is associated with insulin resistance and risk of diabetes. Weight loss reduces ectopic fat deposition and risk of diabetes, but is difficult to sustain to due to compensatory increases in appetite. Fermentable carbohydrates have been shown to decrease appetite and food intake, and promote weight loss in overweight subjects. In animal studies, fermentable carbohydrate reduces ectopic fat independent of weight loss. We aimed to investigate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
58
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 49 publications
9
58
1
4
Order By: Relevance
“…9 It could be suggested that the elevated ratio of colonic propionate : acetate promoted by IPE supplementation may have prevented the accumulation of liver fat observed in the inulin-control group by impairing hepatic acetate metabolism. This proposed mechanism is concordant with the results from Wolever and colleagues, who showed using stable isotope technology that propionate inhibits incorporation of colonic [1,[2][3][4][5][6][7][8][9][10][11][12][13] C] acetate into plasma lipids in humans. 7 Studies using rat hepatocytes have also highlighted that propionate inhibits lipid synthesis when acetate is a major source of acetyl-CoA.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…9 It could be suggested that the elevated ratio of colonic propionate : acetate promoted by IPE supplementation may have prevented the accumulation of liver fat observed in the inulin-control group by impairing hepatic acetate metabolism. This proposed mechanism is concordant with the results from Wolever and colleagues, who showed using stable isotope technology that propionate inhibits incorporation of colonic [1,[2][3][4][5][6][7][8][9][10][11][12][13] C] acetate into plasma lipids in humans. 7 Studies using rat hepatocytes have also highlighted that propionate inhibits lipid synthesis when acetate is a major source of acetyl-CoA.…”
Section: Resultssupporting
confidence: 90%
“…Our previous work showed that 30 g/d ITF supplemented into the habitual diet of overweight adults with normal glycaemic control had no effect on IHCL . In contrast, a superior reduction in IHCL in adults with prediabetes was found when a weight‐loss diet was combined with 30 g/d ITF supplementation . The serendipitous observation in the current study is that supplementing 20 g/d inulin into a habitual weight‐maintaining diet raises IHCL and further exacerbates glucose homeostasis in adults with NAFLD.…”
Section: Resultsmentioning
confidence: 39%
See 3 more Smart Citations